Numerical analysis on the secondary load cycle on a vertical cylinder in steep regular waves. (15th November 2018) - Fan, Xiang; Zhang, Jingxin; Liu, Hua
Abstract: The secondary load cycle induced by regular waves of large amplitude has an important influence on the ringing response of offshore structures. To understand the mechanism of the effect of local violent water deformation of the free surface around a vertical cylinder on the wave loads, the numerical simulations are carried out for the cases of the steep regular waves. The numerical wave tank is established by solving the two-phase incompressible Navier–Stokes equations. The VOF method is applied to capture the violent flow with the free surface near the cylinder. The numerical model is validated by experimental measurement and theoretical result. New characteristic parameters of the secondary load cycle are defined in terms of the amplitude, duration and phase. The effects of wave steepness, relative diameter and relative depth on these characteristic parameters are presented and discussed. The results show that the characteristic parameters depend mainly on relative wave height and relative diameter of cylinder while the dependence on relative depth is weak. Using the fitting method, the empirical formulas are proposed to calculate the characteristic parameters of the secondary load cycle in terms of different wave steepness and relative diameter.